Réponses

  • Utilisateur Brainly
2014-09-17T20:09:56+02:00
A) 
a = 140 ; b = 84 ; a - b = 56 donc PGCD(140,84) = PGCD(84,56)
a = 84 ; b = 56 ; a - b = 28 donc PGCD(84,56) = PGCD(56,28)
a = 56 ; b = 28 ; a - b = 28 donc PGCD(56,28) = PGCD(28,28)
On en conclut que PGCD(140,84) = 28 en 3 étapes.

b) 
a = 108 ; b = 45 ; a - b = 63 donc PGCD(108,45) = PGCD(45,63)
a = 63 ; b = 45 ; a - b = 18 donc PGCD(63,45) = PGCD(45,18)
a = 45 ; b = 18 ; a - b = 27 donc PGCD(45,18) = PGCD(18,27)
a = 27 ; b = 18 ; a - b = 9 donc PGCD(27,18) = PGCD(18,9)
a = 18 ; b = 9 ; a - b = 9 donc PGCD(18,9) = PGCD(9,9)
On en conclut que PGCD(108,45) = 9 en 5 étapes.
2014-09-17T20:18:04+02:00
a) PGCD 140 et 84
140 - 84 = 56
84 - 56 = 28
56 - 28 = 28
28 - 28 = 0
PGCD (140 ; 84) = 28

b) PGCD 108 et 45
108 - 45 = 63
63 - 45 = 18
45 - 18 = 27
27 - 18 = 9
18 - 9 = 9
9 - 9 = 0
PGCD (108 ; 45) = 9